Modifikasi alat cakram untuk proses pembelajaran - Laras Gita Kinanti; Utvi Hinda Zhannisa; Tubagus Herlambang (YLPK Mahardhika, 2021)
The purpose of this research is to modify a simple disc device for learning physical education. The research method used was the development of Borg & Gall, namely (1) collecting information, (2) developing the initial form (in the form of a disc tool model), (3) expert validation testing, namely using 1 validation of athletic experts and one physical education learning expert, and small-scale trials using questionnaires and analysis, (4) revision of the first product design, based on the results of experts and small-scale trials (20 students), (5) field trials (48 students), (6) final product revision, (7) the final result of the modification produced through revision of field trials.The results of expert validation were carried out by 2 validities, namely validation in the field of athletic experts and validation of physical education material experts, and the results obtained in each validity were the first for the validation results in the field of athletic experts getting a percentage of 87.6% calcification (Good) , the second for the validation results in the field of Physical Education material experts got a percentage of 83.0% with the classification (Good). The results of the student questionnaire on a small scale test got a percentage of 86.6% (good). the results of the questionnaire on large-scale test students got a percentage of 81.8% (good).The conclusion and advice is that the development of a modified model of disc throwing tools with iron plate waste media can be used as an alternative to discus throwing. With the modification of disc throwing, teachers and students can be helped in learning discusses, students are interested and more active and excited in learning throw the disc.